A Distinct Variant of Pseudohypoparathyroidism (PHP) First Characterized Some 41 Years Ago Is Caused by the 3‐kb STX16 Deletion. (15th June 2021) - Kiuchi, Zentaro; Reyes, Monica; Brickman, Arnold S; Jüppner, Harald
ABSTRACT: In 1980, Farfel and colleagues ( NEJM, 1980;303:237–42) provided first evidence for two distinct variants of pseudohypoparathyroidism (PHP) that present with hypocalcemia and impaired parathyroid hormone (PTH)‐stimulated urinary cAMP and phosphate excretion, either in the presence or absence of Albright's hereditary osteodystrophy (AHO). An "abnormal allele" and an "unexpressed allele" were considered as underlying defects, predictions that turned out to be correct for both forms of PHP. Patients affected by the first variant (now referred to as PHP1A) were later shown to be carriers of inactivating mutations involving the maternal GNAS exons encoding Gsα. Patients affected by the second variant (now referred to as PHP1B) were shown in the current study to carry a maternal 3‐kb STX16 deletion, the most frequent cause of autosomal dominant PHP1B, which is associated with loss of methylation at GNAS exon A/B that reduces or abolishes maternal Gsα expression. However, the distinct maternal mutations leading to either PHP1A or PHP1B are disease‐causing only because paternal Gsα expression in the proximal renal tubules is silenced, ie, "unexpressed." Our findings resolve at the molecular level carefully conducted investigations reported some 41 years ago that had provided first clues for the existence of two distinct PHP variants. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.